Epidural steroid injections: an updated review on recent trends in safety and complications. (March 2015) - Bicket, Mark C; Chakravarthy, Krishnan; Chang, David; Cohen, Steven P
SUMMARY : Epidural steroid injections (ESIs), which can provide significant but temporary pain relief in well-selected patients, are the most commonly performed procedure in pain management. The anatomy of the epidural space provides a framework for understanding risks associated with ESIs, a topic relevant to both patients and physicians in interventional pain, surgery and primary care. Safety considerations of epidural steroids include drug preparation and myriad physiological effects stemming from steroid exposure. Although major complications associated with ESI occur rarely, potentially catastrophic events resulting from infectious, hematologic and neurologic morbidity may lead to permanent injury. The safety profile of ESIs may improve with development and dissemination of sound injection technique, safer compounds manufactured in a sterile manner and deficient of thromboembolic potential and the application of existing technology.